Lady urologist and male patients with prostate cancer - Rodolfo Montironi; Antonio Lopez-Beltran; Meredith C. Wasserman; Alessia Cimadamore; Liang Cheng (Archivio Italiano di Urologia e Andrologia)
To the Editor